2010
DOI: 10.1590/s0103-64402010000100010
|View full text |Cite
|
Sign up to set email alerts
|

Use of enamel matrix protein derivative with minimally invasive surgical approach in intra-bony periodontal defects: clinical and patient-centered outcomes

Abstract: This case series evaluated the clinical performance and patient-centered outcomes after a minimally invasive surgical technique (MIST) associated with enamel matrix protein derivative (EMD), for the treatment of intra-bony defects. Twelve patients presenting teeth with probing depth >or=5 mm and bleeding on probing associated with radiographic evidence of intra-bony defect were treated by MIST associated with EMD. Clinical parameters were measured at baseline, 3 and 6 months. Patient perception during the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 17 publications
1
39
0
3
Order By: Relevance
“…The studies included a number of subjects ranging between 10 and 87. Only one study did not report the mean age of patients (Harrel, Wilson, & Nunn, ), while eleven did not report the age range of subjects (Aimetti et al, , Ghezzi et al, , Harrel et al, , Harrel, Wilson, & Nunn, , Harrel et al, , Ribeiro, Casarin, Palma, et al, 2011a, Ribeiro et al, , Ribeiro, Casarin, Palma, et al, 2011b, Ribeiro et al, , Schincaglia et al, , Trombelli et al, ). The overall age range of subjects analysed is 25–79 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies included a number of subjects ranging between 10 and 87. Only one study did not report the mean age of patients (Harrel, Wilson, & Nunn, ), while eleven did not report the age range of subjects (Aimetti et al, , Ghezzi et al, , Harrel et al, , Harrel, Wilson, & Nunn, , Harrel et al, , Ribeiro, Casarin, Palma, et al, 2011a, Ribeiro et al, , Ribeiro, Casarin, Palma, et al, 2011b, Ribeiro et al, , Schincaglia et al, , Trombelli et al, ). The overall age range of subjects analysed is 25–79 years.…”
Section: Resultsmentioning
confidence: 99%
“…The minimally invasive surgical technique (MIST) was used in eleven studies by different authors (Aimetti et al, ; Cortelini et al, ; Cortellini et al, ; Cortellini & Tonetti, , ; Cortellini & Tonetti, , ; Cosyn et al, ; De Bruyckere et al, ; Ghezzi et al, ; Ribeiro, Casarin, Palma, et al, 2011a; Ribeiro, Casarin, Palma, et al, 2011b; Ribeiro et al, , ), with the aid of an operating microscope. It consists of an envelope full‐thickness flap extended to the buccal and lingual aspects of the two teeth adjacent to the defect to expose 1–2 mm of the residual bone crest; flaps are then repositioned without any coronal displacement, and the suturing approach consists of a single modified internal mattress suture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Periodontists are clearly aware that pain is an outcome that deserves attention. Quite a number of researchers asked their patients to indicate their level of pain at different points in time after different types of periodontal surgery, 16‐20 or they focused on the degree to which patients reported dentin hypersensitivity after certain procedures 14,19‐21 …”
Section: Enhancing Periodontal Health Through Regenerative Approachesmentioning
confidence: 99%
“…In a case cohort study, Cortellini and Tonetti indicated that a minimally invasive surgical technique combined with EMD in the regenerative treatment of isolated intrabony defects resulted in excellent clinical improvements while limiting patient morbidity 111. The use of a minimally invasive surgical technique with EMD promoted significant improvements in clinical parameters, with minimal pain/discomfort and maximum esthetic satisfaction in the treatment of intrabony defects 112. No additional clinical benefits were apparent when using Emdogain in comparison with sites treated with a placebo (the Emdogain carrier alone) in deep and wide intrabony defects 113…”
Section: Controlled Clinical Studies In Intrabony Defectsmentioning
confidence: 99%